2016
DOI: 10.1111/1475-6773.12586
|View full text |Cite
|
Sign up to set email alerts
|

Physician EHR Adoption and Potentially Preventable Hospital Admissions among Medicare Beneficiaries: Panel Data Evidence, 2010–2013

Abstract: Objective. To test for correlation between the growth in adoption of ambulatory electronic health records (EHRs) Study Design. Fixed effects model estimated the relationship between hospital referral region (HRR) level measures of physician EHR adoption and ACSC admissions and readmissions. Analyzed rates of admissions and 30-day readmissions per beneficiary at the HRR level (restricting the denominator to beneficiaries in our sample), adjusted for differences across HRRs in Medicare beneficiary age, gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Focusing practice purchases toward physicians achieving MU could have benefited organizations by smoothing the assimilation process and by reducing the need for software purchases or training while allowing them to maximize the accompanying subsidies from the HITECH Act. Vertically integrated systems may have also helped facilitate improved quality and coordination of care offered to patients—consistent with some recent evidence …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Focusing practice purchases toward physicians achieving MU could have benefited organizations by smoothing the assimilation process and by reducing the need for software purchases or training while allowing them to maximize the accompanying subsidies from the HITECH Act. Vertically integrated systems may have also helped facilitate improved quality and coordination of care offered to patients—consistent with some recent evidence …”
Section: Discussionsupporting
confidence: 68%
“…Data on ambulatory physicians were from a commercial research firm, SK&A, and included the years 2011, 2013, and 2015, with more than 500 000 physicians represented in each year of the data. SK&A aims to collect information on all office‐based physician practices in the United States via regularly scheduled phone interviews, and this data source has previously been used to measure physician EHR adoption, practice characteristics, and physician integration behavior . We used physician's national provider identifiers (NPIs) to combine these data with the Medicare MU Attestation Eligible Professionals Public Use Files (PUF) (https://www.cms.gov/Regulations-and-Guidance/Legislation/EHRIncentivePrograms/PUF.html) and the Medicare Provider Utilization and Payment Data.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence of an association between HIE and various measures of care is lacking, mixed, and mostly dated . An analysis that is part of the global assessment expanded on this prior evidence by examining data from 2010 to 2013, testing for correlations between the growth in health IT before and after the enactment of HITECH and hospital admissions and readmissions for Medicare beneficiaries with at least 1 of 4 chronic conditions—chronic obstructive pulmonary disease (COPD), congestive heart failure (CHF), diabetes, and ischemic heart disease (IHD) . The analysis found that increases in hospital referral region–level health IT penetration among physicians in ambulatory care settings were correlated with decreases in ambulatory care sensitive condition (ACSC) admissions for these Medicare patients.…”
Section: Implementation Experiencementioning
confidence: 99%
“…There is mixed evidence on the impact of these processes; much of this evidence comes from studies of practices that have volunteered to participate (so may differ from practices that do not volunteer) and/or are located in limited geographic areas (Friedberg et al. ; Lammers, McLaughlin, and Barna ; Sinaiko et al. ; Unruh et al.…”
mentioning
confidence: 99%